2017
DOI: 10.1038/s41598-017-04877-1
|View full text |Cite
|
Sign up to set email alerts
|

Mountain gorilla lymphocryptovirus has Epstein-Barr virus-like epidemiology and pathology in infants

Abstract: Epstein-Barr virus (EBV) infects greater than 90% of humans, is recognized as a significant comorbidity with HIV/AIDS, and is an etiologic agent for some human cancers. The critically endangered mountain gorilla population was suspected of infection with an EBV-like virus based on serology and infant histopathology similar to pulmonary reactive lymphoid hyperplasia (PRLH), a condition associated with EBV in HIV-infected children. To further examine the presence of EBV or an EBV-like virus in mountain gorillas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 68 publications
(61 reference statements)
0
16
0
1
Order By: Relevance
“…Based on population sizes at the time of sample collection, we screened approximately 76% of the Bwindi and 48% of the Virunga habituated gorilla populations, and 32% of the Bwindi and 35% of the Virunga total gorilla population (both habituated and non‐habituated gorillas) for herpesviruses (representing n = 294 individuals from 26 family groups, as determined by visual identification of known individuals). We detected herpesviruses in the beta ‐ and gamma herpesvir inae subfamilies including mountain gorilla‐specific strains of cytomegalovirus 1 (GbbCMV‐1), cytomegalovirus 2 (GbbCMV‐2), rhadinovirus 1 (GbbRHV‐1) and lymphocryptovirus 1 (GbbLCV‐1) (GbbLCV‐1 detailed findings described in Smiley Evans et al, 2017) (Table 1). We did not detect human HSV‐1 in wild‐habituated mountain gorillas using any of our diagnostic methods, including infants with active raised orofacial lesions, previously suspected to be of herpetic origin.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Based on population sizes at the time of sample collection, we screened approximately 76% of the Bwindi and 48% of the Virunga habituated gorilla populations, and 32% of the Bwindi and 35% of the Virunga total gorilla population (both habituated and non‐habituated gorillas) for herpesviruses (representing n = 294 individuals from 26 family groups, as determined by visual identification of known individuals). We detected herpesviruses in the beta ‐ and gamma herpesvir inae subfamilies including mountain gorilla‐specific strains of cytomegalovirus 1 (GbbCMV‐1), cytomegalovirus 2 (GbbCMV‐2), rhadinovirus 1 (GbbRHV‐1) and lymphocryptovirus 1 (GbbLCV‐1) (GbbLCV‐1 detailed findings described in Smiley Evans et al, 2017) (Table 1). We did not detect human HSV‐1 in wild‐habituated mountain gorillas using any of our diagnostic methods, including infants with active raised orofacial lesions, previously suspected to be of herpetic origin.…”
Section: Resultsmentioning
confidence: 69%
“…To date, the only molecularly characterized herpesviruses in wild mountain gorillas are: gorilla lymphocryptovirus (GbbLCV-1), which is suspected to be associated with pulmonary reactive lymphoid hyperplasia in infants with immature or compromised immune systems (Smiley Evans et al, 2017); a cytomegalovirus (GbbCMV), which has unknown clinical etiology (Murthy et al, 2019;Smiley Evans et al, 2016) and a simplexvirus which most closely resembles HSV-2, and also has unknown clinical etiology (Wertheim et al, 2021).…”
mentioning
confidence: 99%
“…The syndrome of atypical lymphoid hyperplasia, one of the most common histological findings in mountain gorilla infants, is suggestive of acute, profound antigenic stimulation, such as is commonly observed in non‐human primates with retroviral infections and in human pediatric patients with Epstein‐Barr virus infections (Jenson, ; Kojima et al, ; Letvin & King, ). Serological surveys in mountain gorillas and other great apes have found a high seroprevalence of EBV‐like lymphocryptoviruses, which are believed to cause lifelong but subclinical infections in adults (Fellinger, Rietschel, & Czerny, ; Kilbourn et al, ; Smiley Evans et al, ; Whittier et al, ). The nature and range of severity of atypical lymphoid lesions in mountain gorilla infants suggest that they may represent a clinical illness.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, new simian enteroviruses have been isolated from chimpanzees, including a D type enterovirus (EV111) that was found phylogenetically related to a human isolate from the DRC (147). It was also recently reported that Mountain gorillas ( Gorilla beringei ) are widely infected (43%) with lymphocryptoviruses (148).…”
Section: Viral Risks For Humans Who Share Ecosystems With Nhpmentioning
confidence: 92%